Studi Literatur Profitabilitas Perusahaan pada Manajemen Modal Kerja dan Struktur Modal - Sartika Sartika; Nurul Mutoharoh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Even though there has been a lot of research on the relationship between working capital and company performance on profitability in Indonesia, the majority of research findings still show the phenomenon of recognizing working capital as an important variable in managing company profitability. This research aims to review, analyze, summarize and present the results of empirical research in Indonesia to help future researchers in making decisions regarding working capital management and capital structure related to company profitability. This literature review examines research that focuses on company performance in terms of profitability, working capital management, and capital structure. The results show that there are varying relationships between working capital and capital structure on profitability so that no agreement can be reached. This study also provides a more in-depth picture to explain this phenomenon and assists research that uses working capital and capital structure in determining its impact on company profitability.